PENGARUH KONEKSI POLITIK, KARAKTER EKSEKUTIF, DAN KOMITE AUDIT TERHADAP PENGHINDARAN PAJAK - Ilma Nursavida; Bambang Wicaksono; Oktavima Wisdaningrum (Accounting Journal of Ibrahimy (AJI), 2023)
This study aims to analyze the influence of political connections, executive character, and audit committees on tax avoidance in mining companies listed on the Indonesia Stock Exchange (IDX) in 2019-2021. The type of data used in this research is secondary data, namely the financial reports of mining companies listed on the Indonesia Stock Exchange for 2019-2021. The sample in this study amounted to 12 companies obtained using the Purposive Sampling method. The results of this study show that political connections have no effect on political connections, executive character has no effect on tax avoidance, and audit committees have no effect on tax avoidance